The Effect of Fascial Suture Type on Postoperative Complications Following Pediatric Gastrostomy Tube Placement - Wilson, Noah; Myers, Emily K; Weber, Nell; Keime, Noah; Becher, Nicole; Tong, Suhong; Prendergast, Connor; Kulungowski, Ann M; Hills-Dunlap, Jonathan L; Diaz-Miron, Jose; Acker, Shannon N (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2025)
A variety of surgical techniques are used to secure the stomach to the abdominal wall during gastrostomy tube (GT) placement. Previous pilot data have demonstrated an increased risk of cellulitis associated with the choice of fascial suture type during gastropexy. We investigated whether fascial suture type impacted rates of common complications after GT placement. We conducted a single-center retrospective review of children who underwent GT placement at the Children's Hospital of Colorado from November 2020 to April 2023. Patients with a concomitant procedure labeled as wound class II or greater were excluded. Subjects were matched 2:1 by suture type to generate a convenience sample. Data collected included patient characteristics and clinical course. Outcomes included cellulitis, tube dislodgement, granulation tissue, ED visits, readmission, and reoperation. Comparisons were made based on fascial suture type, either a polyglactin braided absorbable suture or a poliglecaprone, absorbable monofilament suture. A total of 184 patients were included, 122 in the braided group and 62 in the monofilament group. There were no differences in patient demographics. Neither the rate of granulation tissue at 2 weeks and 6 months nor the median number of granulation tissue events differed between the groups. Rates of cellulitis and tube dislodgement at 2 weeks were similar between the cohorts. Other short-term and long-term outcomes, including GT removal and subsequent gastrocutaneous fistula closure, did not differ. Fascial suture type does not significantly impact the rate of postoperative complications, including rates of cellulitis, granulation tissue, and tube dislodgement following GT placement in pediatric patients.